Factors Influencing Patient Satisfaction with Zambia's National Health Insurance Scheme: A Systematic Literature Review using Empirical Evidence from Nigeria and Ghana - Wesley Mwambazi; Abubaker Qutieshat (Patient Experience Journal)
Universal Health Coverage (UHC) has become important for African nations as they strive to provide equitable healthcare access to all citizens. Implementing a successful National Health Insurance Scheme (NHIS) is crucial to achieving this goal. In pursuit of achieving UHC, Zambia launched the NHIS in 2019 with the ambitious goal of reaching 100% coverage by 2021. Some of those enrolled had reported varying levels of satisfaction with the NHIS services. Understanding patient satisfaction with NHIS-provided services is therefore essential for improving its implementation and enhancing NHIS patient satisfaction. Following PRISMA guidelines, a systematic review of empirical studies from Nigeria and Ghana NHIS on patient satisfaction with NHIS-provided services was conducted to understand its factors. Searches on PubMed and Google Scholar identified 108 papers, of which 20 English peer-reviewed articles published between 2011 and 2023 from Nigeria and Ghana were selected for analysis providing insights into factors influencing NHIS patient satisfaction. These factors were analysed, categorised, and consolidated into shared patterns. Income, age, and education were common factors identified at the socio-demographic level. At the health facility level, waiting times, quality of care, staff attitude, dispensary (drugs), diagnostic services, and out-of-pocket were predominant factors identified. At an individual level, NHIS knowledge was a common factor. Finally, at the health insurance provider level, communication and feedback were a predominant factor. Strategies to increase NHIS patient satisfaction include tailoring NHIS programs to social demographics, reducing wait times, increasing drug supply, improving diagnostics services, providing healthcare staff training, educating patients, enhancing communication and feedback, and promoting NHIS literacy.